Medicinal Applications of Banana Peel Flour Used as a Substitute for Computing Dietary Fiber for Wheat Flour in the Biscuit Industry - Garsa Ali Alshehry (Applied Bionics and Biomechanics)
The aim of this study, medicinal applications of banana peel flour, was used to estimate nutrition value and minerals content. The results indicated that banana peel flour was safe for food application, and it was lower in protein and fat and higher in dietary fiber and total carbohydrate which were 52.68 and 67.25%, respectively. Moreover, the minerals content of phosphorous, potassium, sodium, manganese, and calcium were 217.92, 110.24, 96.43, 85.25, and 80.27 mg/100 g, respectively. Furthermore, the problem of the study investigated the effect of banana peel flour incorporation with wheat flour with 72% extraction to produce biscuit blends at different ratios of 5.0, 10.0, 15.0, and 20.0%, respectively. The nutrition value and mineral content of banana peel flour in biscuits increased gradually in the blends, according to the results. The methods of study of the four biscuit blends were prepared with banana peel flour substituted and wheat flour extraction of 72 percent, and they were compared to a control biscuit. Sensory properties reported that the control biscuit was the highest score followed by blends which had contained 5, 10, and 15% banana peel flour. Meanwhile, the blend of biscuit fortified with 20% was not accepted by panelists. From the color biscuits, the blends containing 5, 10, and 15% banana peel flour had acceptable color, and the blends' color was not acceptable. This may be caused by dark color and high dietary fiber. The texture profile analyzer and physical characteristics were confirmed and gave the same results. The result is that it could be recommended that the banana peel flour, which has high fiber content, produce acceptable biscuits fortified with 5, 10, and 15% and become functional foods. Panelists did not find the 20% blend biscuits to be particularly appealing.